Diagnostic inequalities relating to physical healthcare among people with mental health conditions: a systematic reviewResearch in context - Elisa Liberati; Sarah Kelly; Annabel Price; Natalie Richards; John Gibson; Annabelle Olsson; Stella Watkins; Emily Smith; Serena Cole; Isla Kuhn; Graham Martin (EClinicalMedicine)
Summary: Background: Inaccurate diagnosis of physical health problems in people with mental health conditions may contribute to poorer health outcomes. We review the evidence on whether individuals with mental health conditions are at risk of diagnostic inequalities related to their physical health. Methods: We searched MEDLINE, PsycINFO, Embase, and CINAHL, 1 September 2002–18 Septemebr 2024 (PROSPERO 2022: CRD42022375892). Seventy-nine studies were eligible for inclusion. Risk of Bias (RoB) was assessed using the Newcastle–Ottawa or RoB2 tools and results were presented as a narrative synthesis. Findings: Findings from the included studies suggests that people with mental health conditions face diagnostic inequalities for their physical health. A minority of studies adopted a design that specifically measured professional- and service-related factors associated with diagnostic inequalities. Most studies, however, measured diagnostic endpoints only, meaning that no inference could be made regarding the relative impact of patients' and clinicians’ behaviour in producing inequalities. Interpretation: Further investigations should consider the stage of the diagnostic process at which inequalities occur, to improve knowledge of the mechanisms underpinning diagnostic inequalities, and support the development of targeted improvement interventions. Funding: This study is funded by The Health Foundation’s grant to the University of Cambridge for The Healthcare Improvement Studies (THIS) Institute. Grant number not applicable.